2003
DOI: 10.1007/s00213-002-1374-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MDMA exposure on the conditioned place preference produced by other drugs of abuse

Abstract: MDMA pretreatment reduced the rewarding properties of ethanol. This finding may represent a functional consequence of MDMA-induced neurotoxicity. By extrapolation, human users of MDMA may be exposed to an increase in risks associated with alcohol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 44 publications
2
34
0
1
Order By: Relevance
“…The results of these studies are conflicting in that CPP to cocaine has been found to be enhanced (Fone et al, 2002;Horan et al, 2000), whereas CPP to amphetamine and heroin has been found to be unaffected (Cole et al, 2003) in rats previously treated with MDMA. However, treatment of rats with MDMA reduced formation of CPP to alcohol, an outcome that is similar to that observed for the formation of CPP to sex in this study.…”
Section: Discussionmentioning
confidence: 95%
“…The results of these studies are conflicting in that CPP to cocaine has been found to be enhanced (Fone et al, 2002;Horan et al, 2000), whereas CPP to amphetamine and heroin has been found to be unaffected (Cole et al, 2003) in rats previously treated with MDMA. However, treatment of rats with MDMA reduced formation of CPP to alcohol, an outcome that is similar to that observed for the formation of CPP to sex in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Previous single-dose CPP investigations of MDMA/cocaine interactions have employed designs aimed at assessing the effects of prior MDMA exposure on cocaine CPP. Achat-Mendes et al (2003) observed that a single dose of MDMA produced longlasting effects on cocaine-induced reward, but in a similar paradigm Cole et al (2003) failed to find evidence of any effect of prior MDMA exposure on cocaine CPP. Of course, the limitation of such single dose pretreatment experiments is they do not permit characterization of the full dose-effect function for combined MDMA and cocaine CPP.…”
Section: Discussionmentioning
confidence: 99%
“…MDMA and cocaine, presented separately at low doses, have been shown to elicit CPP in rats (Bardo et al, 1995;Cole et al, 2003;Schechter, 1991). Interestingly, a purportedly neurotoxic dose of MDMA (20 mg/kg, s.c.) administered prior to MDMA CPP testing significantly decreased conditioning at lower doses of the test dose, but not at higher doses of the test dose (Schechter, 1991).…”
mentioning
confidence: 99%
“…Cornish et al 2003;Robledo et al 2004;Schenk et al 2003;Wakonigg et al 2004) and non-human primates (Beardsley et al 1986;Fantegrossi et al 2002;Fantegrossi et al 2004;Lamb and Griffith 1987;Lile et al 2005) suggest that animals will self-administer MDMA. Conditioned place preference, referring to the tendency to spend more time in a chamber associated with an i njection of the drug, was reported to occur in rats given MDMA (Bilsky et al 1990; Cole and Sumnall 2003;Meyer et al 2002). A study that examined the rapidity with which a drug-naive rat descended a runway to obtain an injection of MDMA also found that descent was more rapid when MDMA was available (Wakonigg et al 2004).…”
Section: Drug Dependence and Abuse Liabilitymentioning
confidence: 99%